A mathematical model for naturally aspirated Diesel engines - Lira Cacho, Guillermo (2018)
The fundamentals of a zero-dimensional mathematical are presented model for simulating and diagnosing natural aspiration diesel engines are presented. The model is based on the continuity equation, energy conservation equation and the equation of state. Empirical relations for calculating the heat rejected during combustion and heat transfer to the engine walls are used. During intake and exhaust processes the interchange of gases with the environment is calculated without considering waving phenomena in the engine collectors. The mean pressures and temperatures are calculated as a function of the crankshaft's rotation angles and the instantaneous volume. For the validity of the model, results obtained with experimental values of a mono-cylindrical engine are compared.